PENGEMBANGAN BLOG BUDAYA SEBAGAI SARANA BELAJAR BUDAYA - Prasetiani, Dyah (IZUMI, 2016)
Indonesia is a country that has a diverse culture, ethnicity, language, and rich tourism potentials. However, many people abroad who do not know about the diversity of Indonesian culture. The younger generations were much less aware of even less have sufficient of the richness of the culture of Indonesia. The knowledge about Indonesian culture of Japanese Language Education students Semarang State University, is still inadequate, so they can not be explained to the Japanese society apropiately, not good enough. Therefore students need to be given education by developing blog that contains Indonesian culture which is written in Japanese. The purpose of this study was developing a blog that can be a means of learning the culture. The method used is the Research and Development (R & D), with a step preliminary studies, product development, and product validation testing. Data was collected by questionnaire. Japanese expert validation results towards this blog are considered quite good as a means of studying Indonesian culture with an average score of 2.7 on the aspects of the format, quality, clarity, and clarity of language. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor